2020
DOI: 10.1021/acsanm.0c00531
|View full text |Cite
|
Sign up to set email alerts
|

Aminopropylsilatrane Linkers for Easy and Fast Fabrication of High-Quality 10 nm Thick Gold Films on SiO2 Substrates

Abstract: Fabricating smooth and contamination-free sub-10 nm thick gold layers on dielectric substrates is of interest for a number of applications, including plasmonics, metamaterials, and nanoelectronics. Metallic adhesion layers are often used to facilitate good adhesion between gold and substrates, but at the cost of interfacial alloying and subsequent deterioration of the optical and electrical properties of the thin films. Another approach for promoting adhesion between gold and SiO 2 substrates is the use of sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…After functionalizing the surface with APS, the C 1s spectrum in Figure B was similar to that for the cleaned substrate with a minor contribution at 286.43 eV attributed to C–N. Also, a clear signal appeared in the N 1s spectrum showing (at least) two peaks, which we attribute to freely available amines (−NH 2 ) and hydrogen bonded (--NH 2 ) or protonated (−NH 3 + ) amines (Figure B), in agreement with observations of APTES-functionalized SiO 2 . , However, Heinig et al observed a single -NH 2 peak for XPS measurements on polished silicon wafers (0.2 nm RMS roughness) incubated with APS in water for 30 min. We point out that the amount of --NH 2 and −NH 3 + in relation to −NH 2 is expected to vary in the dry state depending on available surface charges and hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After functionalizing the surface with APS, the C 1s spectrum in Figure B was similar to that for the cleaned substrate with a minor contribution at 286.43 eV attributed to C–N. Also, a clear signal appeared in the N 1s spectrum showing (at least) two peaks, which we attribute to freely available amines (−NH 2 ) and hydrogen bonded (--NH 2 ) or protonated (−NH 3 + ) amines (Figure B), in agreement with observations of APTES-functionalized SiO 2 . , However, Heinig et al observed a single -NH 2 peak for XPS measurements on polished silicon wafers (0.2 nm RMS roughness) incubated with APS in water for 30 min. We point out that the amount of --NH 2 and −NH 3 + in relation to −NH 2 is expected to vary in the dry state depending on available surface charges and hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…(Although the presence of APS on the surface was qualitatively confirmed, the surface coverage was not quantified in any way in those studies.) After binding, the APS layer should ideally be cured by heating to 75 °C to make it stable toward hydrolysis in water (Figures S4 and S5), similarly to films formed by silanes. , Note that this refers to stability after surface binding: APS is perfectly stable in the presence of water while in the solution phase, in contrast to conventional silanes such as APTES. For sulfo-SMCC, hydrolysis may occur in aqueous environments, and the molecule is not easily soluble at high salt concentration, while the hydroxysuccinimidyl group requires a pH of 7–9 for efficient reaction with primary amines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The amino-silanes are frequently used as coupling or crosslinking agents due to the alkoxy groups performing hydrolysis and polycondensation processes in the presence of water. [37,38] The organosilanes that include the amine (NH 2 ) group are hydrolysed almost instantly in water, generating stable aqueous solutions. Besides, they could serve as linking units in attaching other functional groups.…”
Section: Introductionmentioning
confidence: 99%